2011
DOI: 10.1002/jmri.22773
|View full text |Cite
|
Sign up to set email alerts
|

Four‐dimensional velocity mapping of the hepatic and splanchnic vasculature with radial sampling at 3 tesla: A feasibility study in portal hypertension

Abstract: Purpose: To demonstrate the feasibility of PC‐VIPR (Phase Contrast Vastly undersampled Imaging with Projection Reconstruction) for the depiction and hemodynamic analysis of hepatic and splanchnic vessels in patients with portal hypertension. Materials and Methods: Twenty‐four cirrhotic patients (55.9 ± 10.4years) were scanned using 5‐point PC‐VIPR for high spatial resolution imaging with large volume coverage at 3 Tesla (T) using a 32‐channel body coil. Vessel segmentation and hemodynamic visualization include… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(22 citation statements)
references
References 0 publications
0
22
0
Order By: Relevance
“…Recently developed time-resolved 3-or 4-dimensional PC-MRI may soon resolve this problem. [34][35][36] The retrospective design also limited our study. We expect a prospective study with longitudinal observations would strengthen the conclusions of our study.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…Recently developed time-resolved 3-or 4-dimensional PC-MRI may soon resolve this problem. [34][35][36] The retrospective design also limited our study. We expect a prospective study with longitudinal observations would strengthen the conclusions of our study.…”
Section: Magnetic Resonance In Medical Sciencesmentioning
confidence: 99%
“…This approach also avoids the need to acquire numerous double oblique planes needed for 2D phase contrast MRI methods. Volumetric velocity mapping has shown to be well suited for the liver and abdomen vasculature where one comprehensive acquisition is followed by post-processing and flow measurements in specific vessels (31).…”
Section: Discussionmentioning
confidence: 99%
“…Further, a single velocity encoding (venc) setting limited evaluation of flow to the portal and splanchnic venous vasculature. Recent work by Frydrychowicz et al demonstrated feasibility of qualitative flow visualization with high spatial resolution and large volumetric coverage using 3D radial undersampling strategies (31). However, as with other accelerated imaging strategies, there is potential for inaccuracies in flow measurements, which have not been assessed for hepatic flow.…”
Section: Introductionmentioning
confidence: 99%
“…Early studies using Cartesian-based 4D flow approaches for the analysis of the portal vein have shown promising results (27)(28)(29)(30). Similarly, recent studies have validated the use of 3D radially undersampled in 4D flow MRI for visualization and quantification in the abdominal circulation, with very high spatial resolution and large volumetric coverage with an approach termed PV VIPR (Phase Contrast Vastly Undersampled Projection Reconstruction) (25,26). Coupled with 5-point velocity encoding (31) this approach allows for quantifying a wide range of flow velocities, which is particularly advantageous for evaluating the arterial, portal venous and hepatic venous circulation (26).…”
Section: Introductionmentioning
confidence: 96%
“…Emerging time-resolved, three-dimensional (3D), three-directional flow-sensitive MRI ("4D flow MRI") sequences for assessing blood flow to the liver provides simultaneous and spatially co-registered anatomical and hemodynamic information of all vessels within the imaging volume (25)(26)(27)(28)(29)(30). However, assessment of liver hemodynamics using standard 4D flow MRI sequences is challenging due to the need for (a) large volumetric coverage, (b) high spatial resolution, (c) sensitivity to a large spectrum of flow velocities, (d) need for respiratory gating and (e) need for short scan times.…”
Section: Introductionmentioning
confidence: 99%